Insights into the selection of 2D LA-ICP-MS (multi)elemental mapping conditions. Issue 9 (8th August 2019) - van Elteren, Johannes T.; Šelih, Vid S.; Šala, Martin
Abstract : Guidelines how to generate good 2D LA-ICP-MS (multi)elemental maps. Abstract : There are several avenues and schools of thought on how to generate good 2D LA-ICP-MS (multi)elemental maps. Especially with the recent advent of "fast" LA cells and the use of simultaneous ICP-TOFMS detectors, instead of the commonly used sequential ICP-QMS detectors, the playing field has changed radically. Generally, data are generated in line scanning mode by pulsed laser ablation of the surface and ICP-MS sampling (signal integration) of one or more pulses. In the imaging process we may encounter all kinds of imaging artifacts such as blur, smear, aliasing and noise that may deteriorate the image quality. In this paper deeper insights into the selection of optimal conditions for fast and high-quality 2D LA-ICP-MS (multi)elemental mapping are given to circumvent or minimize these artifacts based on a modeling approach.